Local Diversification of Methicillin- Resistant Staphylococcus aureus ST239 in South America After Its Rapid Worldwide Dissemination - Botelho, Ana Maria Nunes; Cerqueira e Costa, Maiana Oliveira; Moustafa, Ahmed M.; Beltrame, Cristiana Ossaille; Ferreira, Fabienne Antunes; Côrtes, Marina Farrel; Costa, Bruno Souza Scramignon; Silva, Deborah Nascimento Santos; Bandeira, Paula Terra; Lima, Nicholas Costa Barroso; Souza, Rangel Celso; Almeida, Luiz Gonzaga Paula de; et al. (Frontiers in Microbiology, 2019)
The global spread of specific clones of methicillin-resistant S. aureus (MRSA) has become a major public health problem, and understanding the dynamics of geographical spread requires worldwide surveillance. Over the past 20 years, the ST239 lineage of MRSA has been recognized as an emerging clone across the globe, with detailed studies focusing on isolates from Europe and Asia. Less is known about this lineage in South America, and, particularly, Brazil where it was the predominant lineage of MRSA in the early 1990’s to 2000’s. To gain a better understanding about the introduction and spread of ST239 MRSA in Brazil we undertook a comparative phylogenomic analysis of ST239 genomes, adding 7 completed, closed Brazilian genomes. Brazilian ST239 isolates grouped in a subtree with those from South American and Western European countries, designated the South American clade. After an initial worldwide radiation in the 1960 to 1970’s, we estimate that ST239 began to spread in South America and Brazil in approximately 1988. This clone demonstrates specific genomic changes that are suggestive of local divergence and adaptational change including agrC variants, and a distinct pattern of virulence-associated genes (the presence of the chp and the absence of sea and sasX). A survey of a geographically and chronologically diverse set of 100 Brazilian ST239 isolates identified this virulence genotype as the predominant pattern in Brazil, and uncovered an unexpectedly high prevalence of agr-dysfunction (30%). ST239 isolates from Brazil also appear to have undergone transposon (IS256) insertions in or near global regulatory genes (agr and mgr) that likely led to rapid reprogramming of bacterial traits. In general, the overall pattern observed in phylogenomic analyses of ST239 is of a rapid initial global radiation,with subsequent local spread and adaptation in multiple different geographic locations. Most ST239 isolates harbor the ardA gene, which we show here to have in vivo anti-restriction activity. We hypothesize that this gene may have improved the ability of this lineage to acquire multiple resistance genes and distinct virulence-associated genes in each local context. The allopatric divergence pattern of ST239 also may suggest strong selective pressures for specific traits in different geographical locations.